Sharing wildlife conservation through 4 billion views on YouTube - Vins, Mark; Aldecoa, Mario; Hines, Hunter N. (Global ecology and conservation, 2022)
YouTube is an online video sharing platform attracting billions of users from global audiences. Videos containing wildlife are an increasingly popular subject, with such content being a valuable tool for educating on wildlife initiatives and having the potential to make a meaningful impact on future conservation. Here we examine the content of videos from the YouTube channel Brave Wilderness. This channel has uploaded 662 videos and counting which in total has recently surpassed 4 billion views for their wildlife-centric and conservation-themed outreach. Brave Wilderness shows diverse biodiversity spanning animals, plants, and microbes from a multitude of habitats, and often highlights under-represented taxa. The content of successful videos, such as those that go viral, can be examined to understand what images and messages resonate with a wide audience, thereby informing conservation practitioners on future outreach efforts. The most popular content on Brave Wilderness includes interactions with diverse species including venomous organisms, charismatic megafauna, and unusual taxa. As internet use continues to expand, and the need for content increases, scientists can benefit from participating with and directly contributing to entertaining and educational digital media efforts beyond traditional means of scientific communication.